2021
DOI: 10.3892/etm.2021.11037
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine kinase inhibitors in breast cancer (Review)

Abstract: Anti-epider mal growth factor receptor (EGFR)-targeted therapy has been intensely researched in the last years, motivated by the favorable results obtained with monoclonal antibodies in HER2-enriched breast cancer (BC) patients. Most researched alternatives of anti-EGFR agents were tyrosine kinase inhibitors (TKIs) and monoclonal antibodies. However, excluding monoclonal antibodies trastuzumab and pertuzumab, the remaining anti-EGFR molecules have exhibited disappointing results, due to the lack of specificity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 65 publications
0
25
0
1
Order By: Relevance
“…The EGF receptor and HER2 are often overexpressed in malignant tumors and are acknowledged for their involvement in tumor growth and progression. 22 Several studies have conceded that epigenetic factors like histone modifications are involved in the regulation of EGF induced EMT. Many studies have reported that HDAC inhibitors abate EMT by upregulating E-cadherin in various solid tumors like ovarian cancer, breast cancer, esophageal cancer, etc., thus suggesting the role of HDAC inhibitors in the therapeutic reduction of EMT.…”
Section: Cell Cycle Analysismentioning
confidence: 99%
“…The EGF receptor and HER2 are often overexpressed in malignant tumors and are acknowledged for their involvement in tumor growth and progression. 22 Several studies have conceded that epigenetic factors like histone modifications are involved in the regulation of EGF induced EMT. Many studies have reported that HDAC inhibitors abate EMT by upregulating E-cadherin in various solid tumors like ovarian cancer, breast cancer, esophageal cancer, etc., thus suggesting the role of HDAC inhibitors in the therapeutic reduction of EMT.…”
Section: Cell Cycle Analysismentioning
confidence: 99%
“…It was shown to be effective even in trastuzumab-resistant tumors. However, until now the results were frustrating, and no other EGFR inhibitor has made it to clinical use in TNBC [ 27 ]. As a common targeted drug, TKIs are less likely to cause toxic effects of traditional chemotherapy such as cumulative bone marrow toxicity, yet it does have a different toxicity profile, as it mainly causes skin and gastrointestinal toxicities, including diarrhea and rashes [ 28 ].The biggest challenge for the application of TKIs in clinical practice is drug tolerance, which has been found to be correlated with the overexpressed ALX in resistant tumors [ 29 , 30 ].…”
Section: Receptor Tyrosine Kinases and Associated Pathwaysmentioning
confidence: 99%
“…[5] These include the use of small molecules that target aberrant signal transduction pathways, such as the dual tyrosine kinase inhibitor lapatinib, which is selective towards factors overexpressed in some solid tumors. [6] More traditional small-molecule antineoplastic natural products include the complex diterpenes paclitaxel and docetaxel, which act as microtubule stabilizers, as well as the anthracycline doxorubicin, which acts as a topoisomera II inhibitor. Capecitabine, a tumor-selective oral fluoropyrimidine prodrug released within neoplastic cells, acts as an antimetabolite and inhibits their growth.…”
Section: Biological Overviewmentioning
confidence: 99%